Implementation of In-House Training in an Elementary School Teachers’ Learning Community in Ambalau Subdistrict, Sintang Regency - Loly Fianda; Priadi Surya (Journal of Educational Sciences, 2026)
This study aims to analyze the effectiveness of learning communities in public elementary schools in Ambalau District, Sintang Regency, focusing on In-House Training (IHT) implementation and the roles of community members in supporting teachers’ professional competence. A qualitative case study approach was employed, involving principals, teachers, facilitators, and school supervisors. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model. The findings indicate that learning communities have potential to support teacher professional development despite geographical constraints and limited resources in the 3T area. IHT is implemented collaboratively across schools each semester through participatory and contextual approaches, enabling teachers to actively plan, implement, and facilitate training activities. This model contributes to teachers’ professional competence, confidence, and sense of ownership of continuous learning. Principals, supervisors, and facilitators play important roles in coordinating, mentoring, and sustaining community activities. However, challenges include inadequate infrastructure, limited funding, and weak communication networks. Overall, learning communities supported by collaborative IHT can strengthen teacher competence in remote elementary schools. Continued institutional support is needed to address contextual limitations and sustain long-term professional development outcomes. As the study covers one district, the findings cannot be broadly generalized.